Multi-level issues in strategy and methods - Dansereau, Fred, 1946-; Yammarino, Francis J., 1954- (Research in multi level issues ;, 2005)
Multi-Level Issues in Strategy and Methods is Volume 4 of Research in Multi-Level Issues, an annual series that provides an outlet for the discussion of multi-level problems and solutions across a variety of fields of study. Using a scientific debate format of a key scholarly essay followed by two commentaries and a rebuttal, we present in this series theoretical work, significant empirical studies, methodological developments, analytical techniques, and philosophical treatments to advance the field of multi-level studies, regardless of disciplinary perspective. Similar to Volumes 1 (Yammarino and Dansereau, 2002), 2 (Dansereau and Yammarino, 2003), and 3 (Yammarino and Dansereau), this volume, Volume 4, contains five major essays with commentaries and rebuttals that cover a range of topics, but in the realms of strategy and research methods.In particular, the five critical essays offer extensive literature reviews, new model developments, methodological advancements, and some empirical data for the study of innovation, strategic performance, upper echelons, latent growth modeling, and intra-class correlations. While each of the major essays, and associated commentaries and rebuttals, is unique in orientation, they show a common bond in raising and addressing multi-level issues or discussing problems and solutions that involve multiple levels of analysis.